Perception of Inclusive School and Perceived Preparedness and Concerns among School Principals in Chandigarh, India - Bansal, Dr. Sneh; Kaur, Harpreet (Voices of Teachers and Teacher Educators, 2021)
School principals are the key participants in creating and transforming schools to meet the needs of children with disabilities. Their beliefs and attitudes towards the education of children with special needs in inclusive settings are key factors in implementing inclusive school programmes. The main aim of this study was to examine how inclusive education is perceived by the school principals of Chandigarh, India. What facilities and support are available in Chandigarh schools for children with disabilities? Besides, the study was undertaken to identify the major challenges viewed by the Chandigarh (Union Territory, India) government school principals that impede the implementation of inclusion. The data was collected from school principals through questionnaires, face-to-face interviews and observations. The results were analysed under four themes: understanding of the concept of inclusion and principal’s contribution in making school inclusive for all, physical and support services in schools, in-service training of the regular teachers in inclusive education and challenges perceived by the principals in the education of disabled children in schools. The results indicated that although principals had a fairly good idea about inclusion, they did not perceive the schools were ready for inclusion of children with disabilities. Lack of infrastructure and materials resources, special educators and support services, noncooperation from parents, large class size, and behaviour problems of children with disabilities were cited as the main concerns. The study reiterated the need for upgradation of physical facilities in the school campus, availability of equipment, materials, and teaching-learning resources as well as training of teachers and availability of services of special educators and other support services for the benefit of children with disabilities. The principals with clear vision and training in inclusive methodology will help to create an environment of acceptance, cooperation, innovation and foster creative solutions for the implementation of inclusive education.